2017
DOI: 10.1155/2017/2071247
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Antimicrobial Effects of a New Fast-Set MTA

Abstract: Purpose. To compare the biocompatibility and antimicrobial effectiveness of the new Fast-Set MTA (FS-MTA) with ProRoot MTA (RS-MTA). Methods. The agar overlay method with neutral red dye was used. L929 mouse fibroblast cells were cultured. The liquid and oil extracts and solid test material were placed on the agar overlay, four samples for each material. Phenol was used as the positive control and cottonseed oil and MEM extracts were used as negative controls. Cytotoxicity was examined by measuring the zones o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
(29 reference statements)
2
13
0
2
Order By: Relevance
“…However, the addition of MPC into CSC caused a significant increase in setting time to nearly 1 h for 10% MPC. A long setting time is a clinical disadvantage as it would increase patient chair-time, which may not be ideal for restless or uncooperative patients (e.g., pediatric patients) and would consequently increase the risk of contamination [23,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the addition of MPC into CSC caused a significant increase in setting time to nearly 1 h for 10% MPC. A long setting time is a clinical disadvantage as it would increase patient chair-time, which may not be ideal for restless or uncooperative patients (e.g., pediatric patients) and would consequently increase the risk of contamination [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…The disc diffusion test, adapted from a previous study [23], was used to measure bactericidal properties. The same bacterial culture of Enterococcus faecalis (ATCC 29212) was used for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity was moderate if the reactivity zone extended specimen up to 1.0 cm, and it was severely cytotoxic when the extending of reactivity zone was further than 1.0 cm beyond specimen. 40…”
Section: Resultsmentioning
confidence: 99%
“…15,27,32,40,41 Studies have shown that MTA is biocompatible, 15,19,27,29,32,34,38,[42][43][44][45][46][47][48] has bactericidal effects, 29,43,44 is noncytotoxic, 45 radiopaque, 30,43 bactericidal, 45 can create an impervious durable seal, 15,25,29,30,38,[44][45][46][49][50][51] is dimensionally stable, 15 has good marginal adaption, 51 and can promote osteogenesis, odontogenesis, cementosis, 15,16,29,32,38,44,[50][51][52][53][54] and the regeneration of periradicular tissues.…”
Section: Introductionmentioning
confidence: 99%